2017
DOI: 10.1007/s12187-017-9456-9
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Material Values Scale for Children (MVS-c) for Use in Early Childhood

Abstract: This study aims to validate the Material Values Scale for children (MVS-c) by Opree et al. (Personality and Individual Differences, 51(8), 963-968, 2011) among children in early childhood. The MVS-c was originally developed to assess materialism among children between the ages of eight to eleven, and consists of three subscales measuring material centrality, material happiness, and material success. We administered the MVS-c to a sample of 120 elementary school children between the ages of six to eight. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…In previous studies, the results for gender differences in materialism were also mixed. Some studies showed that boys are more materialistic than girls (Kasser, 2005;John, 1999), while others showed that there are no gender differences (van der Meulen et al, 2018). In our study, we pointed out that gender differences in General Materialism scores in PMT were primarily due to gender differences in responses to questions about clothing.…”
Section: Discussionsupporting
confidence: 39%
“…In previous studies, the results for gender differences in materialism were also mixed. Some studies showed that boys are more materialistic than girls (Kasser, 2005;John, 1999), while others showed that there are no gender differences (van der Meulen et al, 2018). In our study, we pointed out that gender differences in General Materialism scores in PMT were primarily due to gender differences in responses to questions about clothing.…”
Section: Discussionsupporting
confidence: 39%
“…The MVS-c and its short versions were developed for children between the ages of 8 and 12. Recently, research has also validated the use of the MVS-c and its shorter versions among children aged 6 and 7, for whom it can be used in individual structured interviews using pictorial answer categories (van der Meulen et al 2017). However, because the use of structured interviews is unadvisable for children aged 5 and below (Borgers et al 2000), it does not seem viable to validate the MVS-c in younger age groups.…”
Section: Future Directionsmentioning
confidence: 99%
“…The use of brands to reinforce self-image indicates the early emergence of materialism in preschool children [ 4 ]. Furthermore, research by van der Meulen et al [ 8 ] suggests that children as young as 6 years old are able to understand the symbolic meaning of material possessions. Smith et al [ 9 ] have also shown that children as young as 5 years old have different spending and saving tendencies and can reliably express them.…”
Section: Introductionmentioning
confidence: 99%
“…The Material Values Scale for Children is a self-assessment questionnaire aimed at 8–11-year-old children. This instrument has also been adapted and validated for children aged 6–8 years old by van der Meulen and coworkers [ 8 ]. Because children at this age may have reading difficulties and be suggestible, the instruments developed for this age group are administered individually and the questions are read aloud by the experimenter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation